Algorithms for Dynamic Correction of the Thermal Flows’ Measuring Systems’ - Verlan, A.A.; Sterten, Jo; Furtat, Yu.O. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2016)
Algorithms for thermal flows’ measuring systems’ dynamic correction are considered. The algorithms are based on the solution of deconvolution problem. The algorithms serve as a basis for development of special-purpose computing means for on-line solution of the dynamics faults’ compensation problem in measuring systems.